Sustainable Woodfuel Supplies from the Dry Tropical Woodlands - World Bank (Washington, DC, 2014)
Dry tropical woodlands provide around 80 percent of the energy needs of both urban and rural populations in Africa and are of similar importance on a more localized scale in other areas. They also provide livestock fodder, building poles and many of the daily needs of the rural people living in and around them. Concern about the degradation and depletion of these woodlands date back a long time. Large numbers of woodfuel projects were launched but it soon became evident that many had started with simplistic views of the problems they were addressing. Many of the proposed solutions were impractical or depended on continued inputs on labor and materials not available in the long term. Others made unrealistic demands on local administrations and institutions. Even more importantly, it began to emerge that there were serious flaws in the woodfuel supply and demand analysis on which the great majority of these woodfuel projects were based. This had led to a gradual evolution and change in thinking. The newly emerging consensus suggests that the danger posed by woodfuel harvesting is far less than previously supposed and that the "woodful crisis" has been greatly exaggerated. If the dry tropical woodlands are in danger, it is not because they are being depleted by woodfuel harvesting but because they are of little, if any, economic, as opposed to environmental or social, value. It may be that woodfuel harvesting can provide an economic reason for their preservation.